2001
DOI: 10.1182/blood.v98.12.3241
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia caused by the development of antibodies to thrombopoietin

Abstract: Thrombocytopenia developed in some individuals treated with a recombinant thrombopoietin (TPO), pegylated recombinant human megakaryocyte growth and development factor (PEG-rHuMGDF). Three of the subjects who developed severe thrombocytopenia were analyzed in detail to determine the cause of their thrombocytopenia. Except for easy bruising and heavy menses, none of these subjects had major bleeding episodes; none responded to intravenous immunoglobulin or prednisone. Bone marrow examination revealed a marked r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
379
2
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 637 publications
(391 citation statements)
references
References 27 publications
2
379
2
8
Order By: Relevance
“…145 AEs associated with the use of rhTPO plus G-CSF appear to be similar to those seen with the use of G-CSF alone; 144,145 however, cytopenias owing to neutralizing antibodies to TPO have been reported in a small number of patients who were given rhTPO to treat chemotherapy-induced thrombocytopenia. 146,147 Currently, no TPOs have been approved by the FDA for mobilization. 148 Parathyroid hormone Parathyroid hormone (PTH) activates osteoblasts, which produce hematopoietic growth factors in the stem cell niche, thereby increasing the numbers of circulating stem cells.…”
Section: Novel Agentsmentioning
confidence: 99%
“…145 AEs associated with the use of rhTPO plus G-CSF appear to be similar to those seen with the use of G-CSF alone; 144,145 however, cytopenias owing to neutralizing antibodies to TPO have been reported in a small number of patients who were given rhTPO to treat chemotherapy-induced thrombocytopenia. 146,147 Currently, no TPOs have been approved by the FDA for mobilization. 148 Parathyroid hormone Parathyroid hormone (PTH) activates osteoblasts, which produce hematopoietic growth factors in the stem cell niche, thereby increasing the numbers of circulating stem cells.…”
Section: Novel Agentsmentioning
confidence: 99%
“…107 However, the use of these drugs was complicated by development of antibodies that cross-reacted to native TPO, and in the case of PEG-rHuMGDG recipients, neutralized TPO (resulting in prolonged thrombocytopenia). 108 For this reason, subsequent drug development in this field has focused on finding molecules that either interact with the TPO receptors on the megakaryocyte surface, or stimulate the downstream intracellular signaling pathway that is activated by TPO. Two such molecules have been identified that act to increase platelet counts by stimulating platelet production in megakaryocytes: eltrombopag, a synthetic molecule with oral bioavailability that interacts non-competitively with the TPO receptor to increase thrombopoiesis, 109 and romiplostim, a novel peptide in which two IgG Fc domains are fused to four copies of a TPO-mimetic peptide.…”
Section: Future Considerationsmentioning
confidence: 99%
“…An unwanted consequence of BP therapy is the development of immunogenic responses, which in some cases have little or no impact but in other cases affect safety significantly, with induction of infusion reactions, hypersensitivity reactions and autoimmune syndromes occurring due to cross‐reactivity of anti‐drug antibody (ADA) with endogenous counterparts of the BP 3, 4, 5, 6, and/or decreased efficacy related to neutralization of the BP's biological activity or increasing its clearance 7, 8, 9. For these reasons, immunogenic potential of a BP is determined during clinical trials by measurement and characterization of ADA that develop during treatment; in some cases, monitoring for biopharmaceutical and ADA levels may be conducted during routine use of approved BPs to guide patient care 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%